Influence of co-solvent concentration on the properties of dope solution and performance of polyethersulfone membranes - Ahmed, I. (2013)
Polyethersulfone (PES) dope solutions were prepared from mixtures of two solvents containing N,N-dimethylformamide (DMF) as core solvent and acetone as co-solvent (CS) in a closed heating system. PES asymmetric membranes were cast by a dry/wet phase inversion process. Complete miscibility of PES with the fixed mixture of acetone and DMF under atmospheric pressure could be achieved. The kinetic and thermodynamic properties indicated that interaction of DMF and acetone is strongest when their mole ratio is unity, pointing to the phenomenon of true co-solvency for PES dissolution. These results were supported by determination of the water uptake, contact angle measurement, and SEM analyses. Membrane performance, pore volume, and total pore volume on the membrane surface were also investigated. Â© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.